Increase in glutamate-induced neurotoxicity by activated astrocytes involves stimulation of protein kinase C - Ahlemeyer, Barbara; Kölker, Stefan; Zhu, Yuan; Hoffmann, Georg F.; Krieglstein, Josef (Journal of neurochemistry, 2002)
Activation of astrocytes is a common feature of neurological disorders, but the importance of this phenomenon for neuronal outcome is not fully understood. Treatment of mixed hippocampal cultures of neurones and astrocytes from day 2-4 in vitro (DIV 2-4) with 1 µm cytosine arabinofuranoside (AraC) caused an activation of astrocytes as detected by a stellate morphology and a 10-fold increase in glial fibrillary acidic protein (GFAP) level compared with vehicle-treated cultures. After DIV 12, we determined 43% and 97% damaged neurones 18 h after the exposure to glutamate (1 mm, 1 h) in cultures treated with vehicle and AraC, respectively. Dose-response curves were different with a higher sensitivity to glutamate in cultures treated with AraC (EC50 = 0.01 mm) than with vehicle (EC50 = 0.12 mm). The susceptibility of neurones to 1 mm glutamate did not correlate with the percentage of astrocytes and was insensitive to an inhibition of glutamate uptake. In cultures treated with vehicle and AraC, glutamate-induced neurotoxicity was mediated through stimulation of the NR1-NR2B subtype of NMDA receptors, because it was blocked by the NMDA receptor antagonist MK-801 and the NR1-NR2B selective receptor antagonist ifenprodil. Protein levels of the NR2A and NR2B subunits of NMDA receptor were similar in cultures treated with vehicle or AraC. AraC-induced changes in glutamate-induced neurotoxicity were mimicked by activation of protein kinase C (PKC), whereas neuronal susceptibility to glutamate was reduced in cultures depleted of PKC and treated with AraC suggesting that the increase in glutamate toxicity by activated astrocytes involves activation of PKC.